Al-Ghazali's Sufi Thought as a Foundation of Contemporary Islamic Spirituality: Evidence from Classical and Modern Islamic Discourses - Ghazali, Imam; Jinan, Mutohharun; Najib, Farouq Muhammad (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This article explores the Sufi philosophy of Abu Hamid al-Ghazali as articulated in al-Munqidz min al-Dhalal. It examines the continuing relevance of al-Ghazali's Sufi thought to contemporary Islamic spirituality, with particular emphasis on education and the promotion of religious moderation. Employing a qualitative library-based research method, the study analyzes classical and modern primary and secondary sources. The findings reveal that spiritual purification (tazkiyat al-nafs) and the harmonization of intellect and inner conscience constitute fundamental pathways toward ma'rifatullah. Al-Ghazali's ideas remain significant for cultivating an Islamic spirituality that is rational, moderate, and ethically grounded. These insights advance Islamic studies and educational practice, especially in the design of a holistic educational framework capable of responding to modern spiritual challenges.